Laws on The Management of the Underground Economy in the Criminal Sector in Vietnam - Hung, Nguyen Vinh; Thinh, Tran Cong; Huong, Dao Thi Thu (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2025)
This study explores the complex relationship between criminal law and the underground economy in Vietnam, highlighting both its economic contributions and its detrimental effects on social order, security, and individual well-being. The underground economy—comprising unregistered businesses, informal labor, and illicit trade—has persisted due to gaps in legal enforcement, economic inequality, and the pursuit of profit outside regulatory oversight. While it can stimulate short-term economic activity, it also undermines fiscal stability, erodes trust in public institutions, and exposes participants to significant risks. To analyze this phenomenon, the study employs a qualitative research method that integrates literature review, juridical-normative analysis, and case-based exploration. Legal documents, policy papers, and academic studies are examined to understand how Vietnamese criminal law addresses underground economic activities. In addition, expert interviews with legal scholars, law enforcement officers, and economists provide contextual insights into enforcement challenges and policy gaps. This qualitative approach allows for a nuanced understanding of how law and informal economic practices interact in real-world contexts, beyond mere statistical data. The findings reveal that Vietnam’s criminal law serves not only as a deterrent mechanism but also as a regulatory instrument that shapes economic behavior. However, enforcement remains inconsistent, and coordination among state institutions remains limited. The study concludes with policy recommendations to improve legal frameworks, strengthen institutional capacity, and promote public awareness to manage and gradually formalize the underground economy in Vietnam effectively. REFERENCES Channel 14.Vn Electronic Newspaper (2018). “The story of legalizing prostitution in 10 countries around the world: The country allows prostitution but restricts the purchase of sex”. Access source: https://kenh14.vn/ specializing 20180407163634065.chn, accessed date: February 15, 2025. Dao, X. H., Nguyen, V. H., & Nguyen, D. A. (2023). “Requirements and recommendations to ensure social security for people working in the informal economy sector in Vietnam”. Journal of Namibian Studies, Vol. 33 (2023): Special Issue 3, e-ISSN 2197-5523, Publication date: May-22-2023, DOI: https://doi.org/10.59670/jns.v33i.1970 , https://namibian-studies.com/index.php/JNS/article/view/1970 , p. 932. Department For Social Vices Prevention - Ministry Of Labor, War Invalids And Social Affairs (2020). “The fates of Japan's red light district during the pandemic”. Access source: http://pctnxh.molisa.gov.vn/default.aspx?page=news&do=detail&id= 2742, accessed date: February 25, 2025. Economichelp. (2019). “Underground Economy - definition, problems and causes”. Access source: https://www.economicshelp.org , accessed date: February 25, 2025. Friedrich, S., & Robert, K. (2004). “Shadow economies around the world: What do we khow?”. CESifo Working Paper NO. 1167, Category 1: Public finance, April 2004. Hung , N. V., Thinh , T. C., & Duy, N. D. (2022). Cooperative Group In Current Vietnamese Commercial Environment. International Journal of Professional Business Review, 7(6), e0509, Access source: https://doi.org/10.26668/businessreview/2022.v7i6.e509 , p. 01. Hung, N. V. (2023). “Characteristics of the underground economy in Vietnam”. Lex Humana (ISSN 2175-0947), 15(3), access source: https://seer.ucp.br/seer/index.php/LexHumana/article/view/2537 , p. 18. Le, C., And NGUYEN, T. L. (2014). “Death Penalty in Vietnam’s Criminal Code: To Retain or Reduce and Eventually Abolish?”. Vietnam National University Journal of Science, Vol. 33 No. 3. National Assembly. “Criminal Code 1999 (amended and supplemented in 2009)”. National Assembly. “Criminal Code 2015 (amended and supplemented in 2017)”. Nguyen Vinh Hung (editor 2021). “Civil issues: Theoretical - Procedure - Comment”, People's Publish Security Publishing House. Nguyen, N. C. (2022). “Commentary on offenses against economic management order in the 2015 Criminal Code, amended and supplemented in 2017. National Political Publishing House, Hanoi. Nguyen, V. H. (2019). “The impact of the underground economy on the economy, society, and law”. Journal of Economic Studies, 7 (03). Nguyen, V. H. (2023_1). “Underground economy in the context of the fourth industrial revolution”. Journal of Political Theory, No.13. Nguyen, V. H. (2023_2). “Law on the management of the underground economy in Vietnam”. Topic scientific research in level school, Vietnam National University, Hanoi, University of Law. Nguyen, V. H., Nguyen, L. T & Tran C. T. (2023). Laws on the management of the underground economy in the financial sector in Vietnam, Lex Humana. Vol. 15 No. 4 (2023), ISSN 2175-0947, Publication date: July 20, 2023, https://seer.ucp.br/seer/index.php/LexHumana/article/view/2737 , p. 241. Nguyen, Vinh. H. (2020). “Managing the type of